Moisture sorption isotherms and thermodynamic properties of walnut kernels - Togrul, Hasan; Arslan, Nurhan (Pergamon-Elsevier Science Ltd, 2007)
The moisture sorption isotherm data of walnut kernels stored in a chamber, the relative humidity (r.h.) of which is regulated by atomizing humidifier, were determined at three different temperatures (25, 35 and 45 degrees C) and r.h. ranging from 10% to 90%. Eight models, namely the GAB, BET, Henderson, Iglesias and Chirife, Oswin, Peleg, Smith and Caurie equations, were fitted to the sorption data. Several statistical tests were adopted as the criteria to evaluate the fitting performance of the models. Of the models tested, the Peleg model gave the best fit to experimental data. The surface area of a monolayer was calculated. The BET equation was applied to the monolayer moisture content and the corresponding a, values at which a monolayer forms are presented. The experimental data were also used to determine the thermodynamic functions such as isosteric heat of sorption, sorption entropy, spreading pressure, net integral enthalpy and entropy. The sorption isosteric heats for walnut kernels were determined by the application of the Clausius-Clapeyron equation to sorption isotherms obtained from the best-fitting equation. Isosteric heats decreased with increase in moisture content and approached the latent heat of pure water. Adsorption entropy increased with increasing moisture content, and then it decreased sharply with increase in moisture content. The spreading pressures (adsorption and desorption) increased with increasing water activity. Net integral enthalpy of adsorption increased slightly with moisture content to a maximum value. Thereafter, it remained constant. Net integral entropy of adsorption was negative in value and it decreased with increase in moisture content to a minimum value, and then increased slightly with increase in moisture content. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: walnut kernels; moisture sorption; isotherms; thermodynamic; atomizing humidifier